Bioconversion of Oil Palm Waste into Protein-Based Bioplastic Using BSF (Hermetia illucens) Larvae - Muhammad Gunawan; Intan Rohyana Devi; Maharana; Maharani; Rudy Agung Nugroho (SEAMEO BIOTROP, 2026)
This study addressed the environmental challenge of palm oil waste by utilizing Oil Palm Empty Fruit Bunch (OPEFB) and Oil Palm Kernel Cake (OPKC) as substrates for Hermetia illucens (Black Soldier Fly) larvae bioconversion. The larvae were cultivated after OPEFB pre-treatment through milling, hydrolysis, and saccharification with Aspergillus niger to enhance digestibility. Protein extracted from larvae was used to produce protein-based bioplastics. Result showed consistent larval growth and consumption rates but variation in waste reduction efficiency, with the 7:3 substrate ratio yielding the highest reduction. Bioplastics exhibited good elasticity and biodegradability, while protein enrichment improved mechanical strength and reduced water absorption. This approach demonstrates a sustainable alternative for managing palm oil waste and producing eco-friendly bioplastics.